2000
DOI: 10.1074/jbc.275.14.10278
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mOAT-mediated Organic Anion Transport by Okadaic Acid and Protein Kinase C in LLC-PK1 Cells

Abstract: Organic anion transporters in the kidney proximal tubule play an essential role in eliminating a wide range of organic anions including endogenous compounds, xenobiotics, and their metabolites, thereby preventing their potentially toxic effects within the body. We have previously cloned a cDNA encoding an organic anion transporter from mouse kidney (mOAT) (Lopez-Nieto, C. E., You, G., Bush, K. T., Barros, E. J. G., Beier, D. R., and Nigam, S. K. (1997) J. Biol. Chem. 272, 6471-6478; Kuze, K., Graves, P., Leahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 31 publications
4
87
0
Order By: Relevance
“…Therefore, these data clearly indicated that PKC activation can result in downregulation of basolateral organic anion transport. Several studies supported this observation, the first of which focused on regulation of mOat1 stably expressed in a porcine renal proximal tubule cell line, LLC-PK 1 [101]. It was demonstrated that PKC activation decreased V max and reduced mOat1-mediated transport of PAH, although direct phosphorylation of mOat1 by PKC was not observed.…”
Section: Phosphorylationmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, these data clearly indicated that PKC activation can result in downregulation of basolateral organic anion transport. Several studies supported this observation, the first of which focused on regulation of mOat1 stably expressed in a porcine renal proximal tubule cell line, LLC-PK 1 [101]. It was demonstrated that PKC activation decreased V max and reduced mOat1-mediated transport of PAH, although direct phosphorylation of mOat1 by PKC was not observed.…”
Section: Phosphorylationmentioning
confidence: 92%
“…Finally, serine/threonine phosphatases have been shown to increase p-aminohippurate (PAH) uptake by an undetermined mechanism. Thus far, the relevance of OAT regulation by direct phosphorylation of the transporter is virtually unknown mOat1 function, and this was indeed because of direct phosphorylation of the mOat1 protein [101]. Others demonstrated that activation of PKC decreased PAH secretion in an opossum kidney cell line as a result of reduction in both renal basolateral uptake and apical efflux [102].…”
Section: Phosphorylationmentioning
confidence: 99%
“…The presence of these conserved phosphorylation sites suggested that OAT might be subject to phosphorylation-induced functional regulation. You and co-workers (You et al, 2000) have shown the involvement of reversible phosphorylation in regulating the function of mOAT1. Okadaic acid, a protein phosphatase inhibitor, significantly increased the level of mOAT1 phosphorylation and it enhanced the phophorylation in a dose-dependent and time-dependent manner that was closely correlated to the decreased PAH transport.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the net secretory transport of organic anions by bradykinin and phenylephrine via PKC was shown in isolated perfused rabbit proximal tubules (23). Recently, You et al (20) showed that PKC inhibits murine OAT without direct phosphorylation of the transport protein itself.…”
mentioning
confidence: 99%
“…Inhibition of basolateral organic anion transport by stimulation of protein kinase C (PKC) was reported in isolated tubules of killifish (18). rOAT3 from rat is also inhibitable by PKC (19), and mOAT from mouse is regulated by PKC and phosphatases (20). The basolateral exchanger of organic anions and dicarboxylates in isolated proximal tubules of rabbit kidney was shown to be regulated by Ca 2ϩ /calmodulin-dependent protein kinase II, thyroxin kinase, phosphatidylinositol-3-kinase, and mitogen-activated protein kinases (MAPK) (21).…”
mentioning
confidence: 99%